PENGARUH EKSTRAK KOPI ROBUSTA TERHADAP EKSPRESI OSTEOKALSIN PADA OSTEOBLAS SELAMA PERGERAKAN GIGI ORTODONTI - Herniyati Herniyati (Universitas Gadjah Mada, 2016)
The objective of research is to determine the expression of osteocalcin on osteoblasts during orthodontic tooth movement after administration robusta coffee extract. Materials and Methods: 16 rats were divided into 2 groups: group K: rats applied with orthodontic mechanical force (OMF) and group P: OMF + coffee robusta extract of 20mg /100 g of BW. OMF was conducted by applying ligature wire on permanent maxillary right first molar and both permanent maxillary incisivus. Subsequently, the permanent maxillary right first molar moved to mesial with Ni-Ti orthodontic closed coil spring. Observations were made on day 15 by immunohistochemical examination to determine the expression of osteocalcin. Results: Robusta coffee extract improved the expression of osteocalcin in the compression and tension areas (p <0.05). Expression of osteocalcin in tension area larger than that in compression area (p <0.05). Conclusion: The administration of Robusta coffee extract increases the expression of osteocalcin, which can increase alveolar bone remodeling.